ECONOMIC EMPOWERMENT STRATEGY OF THE YOUNGER GENERATION THROUGH DIVERSIFICATION OF MULTIPLE BUSINESS BUSINESSES IN INCREASING ECONOMIC GROWTH IN UTAMA RAYA BEACH, SITUBONDO - Moh. Idil Ghufron; Ismi Lailiyatil Wardah; Maudy Sulis Setya Ningsih (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
This research discusses economic empowerment strategies for the younger generation in Situbondo district. In this contemporary era, the problems faced by the younger generation, especially in Situbondo regency in finding work, have become an increasingly deep and troubling issue. This is related to the lack of skills possessed by the younger generation who incidentally are in the Pantura area and consider that the profession as a fisherman is not in accordance with the lifestyle of the younger generation today. This factor causes the younger generation to face difficulties in finding jobs that suit their wishes. Another factor that contributes to this problem is the lack of employment because it is included in the Pantura Area. Utama Raya Beach stands with business diversification, including gas stations, rest areas to lodging utilizing sea destinations on the north side of its business place. The purpose of this study is to explain the strategy of empowering the younger generation in improving the economy in Situbondo district and knowing the new business model through multiple business differentiation.The research methods used include surveys, interviews, and secondary data analysis to get a comprehensive picture of millennials' economic empowerment and the challenges they face. The results of this study show that the multiple business-based business diversification strategy has succeeded in attracting the interest of the younger generation because the business offer from the management has succeeded in attracting the interest of the younger generation in Situbondo